(3GdQSGdI GdbdejIs - (3fYeg Gddg Hf YKeGfs
(3ChdgG (B:s
(3GeG HYO, aEfi bO SeYJ ef Ggd GdHQGYg Ghd eGNdbg Gddg hUag GdhUGahf hcJHhG ai Mbg QSGFd hLYdhgG dYQV MGdge MWi HHGdi s
(3BNQgG (B:s
(3hBNQgG HYfhGf (B((3UaGJg GdfSHjI(B) (3GdcJGHi, GdcGZOi GdeOGOi , GdOhGffi , GdMQhai s
(3hHgGeTgG HYV GdJYdjbGJ hGdTQhMs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B36 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs